Silvering (Slowly). Augmentation, Age, and Mattering - Tapuni, M; Patel, R; O'Hara, Emily; Gallagher, S; Douglas, C (Architecture Art and Design Research (AADR), 2020)
Silvering (slowly) was a group show at St Paul St Gallery in Auckland, NZ, 9–13 September, 2019. It drew together threads from our independent research trajectories as a response to IDEA Journal’s questions around augmentation and technicity. The exhibition was a material dialogue consisting of installations and drawings, structured dialogues before and during the show, and an epistolary exchange afterwards. The operative methodology is one of conversation (between the participants, but conceived more generally as an open-ended material practice that includes nonhuman participants). Without purporting to offer a single consistent position, we problematise the concept of augmentation through our conversation. By means of our rhetorical figures — the moon, mirrors, silvering hair, and silence, we question the time and matter of augmentation, and its sense of forwardness and addition.
Keywords: Spatial design; Materiality; Reflections; Installation; Line